Clinical and Histological Features of Ovarian Hypoplasia/Dysgenesis in Alpacas - Arroyo, Eduardo; Patiño, Cristian; Ciccarelli, Michela; Raudsepp, Terje; Conley, Alan; Tibary, Ahmed (Frontiers in Veterinary Science, 2022)
Alpacas have a high incidence of congenital reproductive tract abnormalities, including ovarian hypoplasia/dysgenesis. Diagnosis of this condition is often challenging. The present study describes the clinical, ultrasonographic, and histologic features of ovarian hypoplasia/dysgenesis syndrome in 5 female alpacas. Additionally, serum AMH levels were compared between female alpacas diagnosed with ovarian hypoplasia/dysgenesis and a group of reproductively sound females (n=11). The syndrome was suspected based on the presence of an infantile uterus and lack of ovaries by ultrasonography and laparoscopy. Four females had normal karyotype, and one presented a minute chromosome. The ovaries from these cases showed 3 main histological classifications: hypoplasia (n=2), dysgenesis (n=2), and dysplasia (n=1). Serum AMH levels in affected females were significantly lower (P<0.05) than those of reproductively sound control females. In conclusion, Serum AMH level may be helpful in the rapid diagnosis of ovarian hypoplasia/dysgenesis syndrome in alpacas. Furthermore, this syndrome in alpacas presents a variety of histological features. Different mechanisms may be involved in the derangement of ovarian differentiation. Further studies are needed to elucidate the causes of the syndrome.